On screening and the insider threat - a methodological exploration - De Valk, Giliam (Array, 2020)
An under researched issue in security is screening combined with the insider threat. One of the problems is the lack of data. Human Resource Management (HRM) departments don’t like to disclose cases and modus operandi. Also the filing is incomplete. It leads to a situation in which theory building is hardly possible. Therefore, this explorative essay is written from a more methodological perspective. From the scarce information that was obtained from expert practitioners, there seems not to be such a thing as a standard profile of an insider threat. At the same time, an estimated 75% of the offenders has shown to have been actually bona fide at the original pre-employment screening. It calls for a reflection on current screening practices. Such an approach has its limitations. Scenarios for offenders cannot be built, because the causes are too diverse and the cases too unique. As files are hardly kept – and HRM departments are not so willing to share – a big data approach is also not a likely option. A way out could be to test the loyalty of employees. In such a system, the emphasis will be on a so-called during-employment screening. The interviewer, together with the applicant, will assess the applicant’s vulnerabilities. After this assessment, the applicant will be tested on his/her vulnerabilities during his/her entire career, Also, there needs to be a shift in the culture at HRM departments. They have to change from steering on mistakes, into being a safety net for employees that have (personal) problems. It also implies a change in interaction – from discussion to dialogue. Finally, in a working environment that is evolving towards a more networked way of working – compared to the classic hierarchical office work – the rethinking concerning the screening practices will only be the more pressing.